Effects of Remote Ischemic Preconditioning in Patients Undergoing Off-Pump Coronary Artery Bypass Graft Surgery - Wang, Huilin; Lyu, Yi; Liao, Qingwu; Jin, Lin; Xu, Liying; Hu, Yan; Yu, Ying; Guo, Kefang (Frontiers in Physiology, 2019)
Purpose This study aimed to evaluate effects of remote ischemic preconditioning (RIPC) on myocardial injury in patients undergoing off-pump coronary artery bypass graft surgery (OPCABG). Methods Sixty-five patients scheduled for the OPCABG were randomly assigned to control (n = 32) or RIPC group (n = 33). All patients received general anesthesia. Before the surgical incision, RIPC was induced on an upper limb with repeated 5-min ischemia and 5-min reperfusion for four times. Blood samples were collected from right internal jugular vein. Plasma levels of IL-6, IL-8, IL-10, TNF-α, cTnT, HFABP, IMA, and MDA were detected at pre-operatively and 0, 6, 18, 24, 48, 72, and 120 h after the surgery. Left internal mammary artery (LIMA) and great saphenous vein (GSV) was cut into 2–3 mm for Western blot analysis of Hif-1α. Results In the present study, RIPC treatment significantly reduced plasma levels of cardiac troponin T (p < 0.05), heart-type fatty acid binding protein (p < 0.05), ischemia modified albumin (p < 0.05), malondialdehyde (p < 0.05), as well as plasma levels of pro-inflammatory cytokines including IL-6, IL-8, and TNF-α (P < 0.05, respectively). RIPC treatment significantly increased hypoxia-inducible factor-1α (p < 0.05) expression as well. Mechanical ventilation time for postoperative patients was shortened in RIPC group than those in control group (17.4 ± 3.8 h vs. 19.7 ± 2.9 h, respectively, p < 0.05). Conclusion RIPC by upper limb ischemia shortens mechanical ventilation time in patients undergoing OPCABG. RIPC treatment reduces postoperative myocardial enzyme expression and pro-inflammatory cytokine production. RIPC is a protective therapeutic approach in the coronary artery bypass graft surgery.